Burn Patients’ Need for Human Caring: Content Analysis Study - S Mohammadhossini; M Gheibizadeh; A Saki Malehi; K Zarea (Armaghane Danesh Bimonthly Journal, 2019)
Abstract Background & aim: Caring is a science that encompasses human beings, reflecting experiences and phenomena in caring including: art and humanity. Humanity in the interpersonal interactions of the heart and the spirit of care and is an opportunity care for humanity to emerge and grow.  The purpose of this study was to determine the human care needs of burn victims.